Rehabilitation approach and results of using the biofeedback method (GIGER MD device) in children with neurogenic bladder - Cvitkovic-Roic, Andrea; Mikulic, Danijel; Turudic, Daniel; Milosevic, Danko; Roic, Goran; Matijevic, Valentina (Frontiers in Neurology, 2023)
Background GIGER MD device applies a biofeedback method through stimulated coordinated rhythmic and dynamic movements of the trunk and extremities in an anti-gravity position, thus helping to regain lost motor functions. Methods In this article, the performance of the GIGER MD device was evaluated in 36 children with neurogenic bladder measuring gait speed, voiding bladder capacity, deviation from the age-adjusted bladder capacity (measured using the Koff scale), and urinary incontinence. Results Children using the GIGER MD device had an increase in voiding bladder capacity (33.79%, median volume increase of 50 ml) with a subsequent median decrease in median age-adjusted bladder capacity by 45.50% (median deviation before was 36% vs. 16% after treatment). The number of urinary incontinence episodes also reduced by 55.57% (7–3 episodes per day), and the 20-meter motor gait speed increased by 14.26% (from 23 to 19 s). Conclusion Children who follow the GIGER MD therapy regularly for a period of 6 months show that CNS functional damage can be significantly improved.